Design and development of a detopping mechanism for onion detopping machine - Carolin Rathinakumari , A; Senthil Kumaran, G (Journal of Horticultural Sciences, 2024)
Onion detopping is one of the unit operations involved in the cultivation of onion crop. Manual onion detopping is time consuming and highly drudgery. Therefore, an onion detopping machine was designed and developed for higher efficiency. An efficient detopping mechanism designed to achieve the maximum performance parameters in terms of detopping efficiency, per cent damage of onion bulbs and capacity of the onion detopping machine. By considering the crop parameters and functional requirement, four types of shearing designs of detopping tool namely, lead screw, square shaft with two cutting edges, square shaft with four cutting edges and helical roller were designed, developed and evaluated. Among four different shearing mechanisms, the helical roller type detopping tool was found to be effective in detopping the onion leaves. The helical roller type detopping tool had a detopping efficiency (98.44±1.07%), per cent damage (2.05±0.45%), conveying efficiency (97.60±1.02 %) and capacity (372.60±13.95 kg/h), respectively